What influences banks’ choice of credit risk management practices? Theory and evidence - Bülbül, Dilek; Hakenes, Hendrik; Lambert, Claudia (Journal of Financial Stability, 2019)
Banks use different risk management practices with varying levels of sophistication. This paper examines the factors that determine the choice of risk-management practices. In a theoretical model, we identify two main determinants for the choice of risk management tools: bank competition and sector concentration in the loan market. We empirically test the predictions of our model using hand-collected data on the credit risk management of 249 German savings banks. The results are in line with our theory: Competition pushes banks to implement advanced risk management practices. Sector concentration in the loan market promotes credit portfolio modeling, but it inhibits credit risk transfer.